ANALISIS KEUNTUNGAN USAHA â€œSARABAâ€ DI RUMAH MAKAN STEVANNY DI KAWASAN BOULEVARD KOTA MANADO - Priscilia Indriani Runturambi; Ribka Magdalena Kumaat; Juliana Ruth Mandei (Sam Ratulangi University, 2018)
This study aims to analyze the profit received by the owner, producer and seller of the business